2019
DOI: 10.2140/agt.2019.19.965
|View full text |Cite
|
Sign up to set email alerts
|

Topological Hochschild homology and higher characteristics

Abstract: We show that an important classical fixed point invariant, the Reidemeister trace, arises as a topological Hochschild homology transfer. This generalizes a corresponding classical result for the Euler characteristic and is a first step in showing the Reidemeister trace is in the image of the cyclotomic trace. The main result follows from developing the relationship between shadows [Pon10], topological Hochschild homology, and Morita invariance in bicategorical generality.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…In [31], Ponto and Shulman showed that classical Hochschild homology extends to a shadow. In [13] Campbell and Ponto proved that topological Hochschild homology of ring spectra and of spectral categories does so as well. In this section, we generalize these result to any nice enough symmetric monoidal, simplicial model category.…”
Section: Hochschild Shadowsmentioning
confidence: 97%
See 4 more Smart Citations
“…In [31], Ponto and Shulman showed that classical Hochschild homology extends to a shadow. In [13] Campbell and Ponto proved that topological Hochschild homology of ring spectra and of spectral categories does so as well. In this section, we generalize these result to any nice enough symmetric monoidal, simplicial model category.…”
Section: Hochschild Shadowsmentioning
confidence: 97%
“…naturally, for all A M B and B N A . It is straightforward to check the remaining shadow conditions, by an argument analogous to that in [13].…”
Section: Hochschild Shadowsmentioning
confidence: 99%
See 3 more Smart Citations